2015
DOI: 10.1039/c4cc07790c
|View full text |Cite
|
Sign up to set email alerts
|

A diarylethene as the SO2 gas generator upon UV irradiation

Abstract: A closed-ring isomer of a diarylethene having a sulfone group works as the reagent for SO2 gas generation with thermal stability even at 70 °C, and it rapidly reverts to the open-ring isomer and generates the SO2 gas to induce cell death upon UV irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…12,13 During the study we found by chance that one of the diarylethene derivative generated SO 2 gas accompanied with decomposition by UV irradiation, thus inducing cell death. 14 On the other hand, on the film of diarylethene derivative 1o, which shows high fatigue resistance without decomposition, 15 we also found a photoinduced cell death upon UV irradiation by a different mechanism. In this study, we examined the photo-toxicity of the diarylethene photoswitch itself upon light irradiation.…”
Section: Madin-darby Canine Kidney (Mdck) Cells Through Caspase Cascamentioning
confidence: 73%
See 1 more Smart Citation
“…12,13 During the study we found by chance that one of the diarylethene derivative generated SO 2 gas accompanied with decomposition by UV irradiation, thus inducing cell death. 14 On the other hand, on the film of diarylethene derivative 1o, which shows high fatigue resistance without decomposition, 15 we also found a photoinduced cell death upon UV irradiation by a different mechanism. In this study, we examined the photo-toxicity of the diarylethene photoswitch itself upon light irradiation.…”
Section: Madin-darby Canine Kidney (Mdck) Cells Through Caspase Cascamentioning
confidence: 73%
“…S1). 14 Although the areal density of diarylethene was much larger (> 100 times) than the case using monomeric 1c, the same dosage of 246 nm of UV light irradiation did not result in observable cell damage. The cells in the photoirradiated area remained as well as those in the non-irradiated area (Fig.…”
Section: Madin-darby Canine Kidney (Mdck) Cells Through Caspase Cascamentioning
confidence: 92%
“…Sumaru and Uchida's group later reported another UV light triggered SO 2 donor based on a dithienylethene structure and demonstrated its application in inducing cell death “on demand” (Scheme 3 ) (Kodama et al, 2015 ). Close-ring compound 9c was found to be stable upon heating up to 70°C.…”
Section: So 2 Donors and Prodrugsmentioning
confidence: 99%
“…In a third strategy, benzosulfones were reported as photochemically activated SO 2 donors by our group and others (Scheme ) . These compounds might have limitations due to the inconvenience associated with using a light source in cellular studies and possibly to the intensity of the light that was required for SO 2 generation . Xian et al.…”
Section: Introductionmentioning
confidence: 99%